Influence of Brand Image and Product Quality Towards Customer Loyalty Among High School Students Using Xiaomi Brand Smartphones in South Tangerang - Widodo, Arif Siaha; Hady, Hamdy; Muharam, Hari (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This research aims to test how big the influence of branding is on customer loyalty. To test how much influence product quality has on customer loyalty. To test how much influence customer satisfaction has on customer loyalty. To test how big the influence of brand and product quality and customer satisfaction simultaneously on customer loyalty among high school students using Xiaomi brand smartphones in the city of South Tangerang. The method approach used in this research is a quantitative approach. The population used in this research were high school students who using Xiaomi brand smartphones in South Tangerang. The sample consisted of 388 respondents. The sampling technique uses accidental sampling using the Slovin formula in determining the number of samples. Meanwhile, the data analysis method tests research instruments using validity tests, reliability tests. Data analysis techniques consist of descriptive analysis of respondent characteristics and SEM Lisrel analysis. The results of this research show that brand image influences customer loyalty with positive and signifiant, product quality has positive and significant effect on customer loyalty, customer satisfaction has positive and significant effect on customer loyalty. Brand image, product quality and customer satisfaction simultaneously influence on customer loyalty with positive and significant.